Peningkatan Sikap Rasa Percaya Diri Peserta melalui Metode Eksperimen di SDN 56/I Desa Aro - Pertiwi, Diah; Khoironi, Dwi Rahmat; Depra, Lola; Afdiya, Putri; Destrinelli, Destrinelli (MASALIQ, 2023)
This study aims to examine the increase in students' self-confidence in learning activities at SDN 56/I Desa Aro. experiment. The type of this research is classroom action research, using a qualitative research type using research subjects are class VI students, totaling 21 students. Data collection was obtained by using observation techniques. The data analysis technique used is descriptive qualitative data analysis. From the research conducted, it was found that the ability of children's self-confidence developed according to expectations. Based on the results of the study, it was shown that the experimental method could improve the self-confidence of students at SDN 56/I in Aro Village.